31 The Effect of Increasing Inclusion of Hempseed Meal on Fiber Digestibility and Performance in Meat Rabbits. (8th March 2022) - Verret, Emily G; Smith, W Brandon; Runyan, Cheyenne L; Jacobson, K June June; Owsley, Frank F; Kinman, Lea Ann A; Muir, James P P
Abstract: Legalization of hemp production in the United States shows potential for utilizing hempseed meal (HSM) as an effective byproduct feedstuff. Our objective was to determine total-tract fiber digestibility of rations containing increasing percentages of HSM in meat rabbits. Thirty-two Californian rabbits, assigned randomly to one of four treatments, were used in a generalized complete block design experiment with two 35-d feeding periods. Treatments replaced soybean meal and alfalfa such that 0%, 25%, 50%, and 75% CP was replaced by HSM. Diets were isonitrogenous and contained 28% steam-flaked corn. Weights were collected every 7 d, and total feed, orts, and fecal samples were collected in the final 7 d of feeding for digestibility determination. Rabbits were harvested after feeding periods, and stomach (S) and cecum (C) content sampling was conducted. Feed, orts, and fecal samples were assayed for DM and fiber fractions for digestibility determination. There was no effect of dietary treatment on DMD (52.5%; P = 0.05), NDFD (-29.5%; P = 0.54), or ADFD (-57.7%; P = 0.56). There was also no effect of dietary treatment on S NDF (11.9 g; P = 0.62), S ADF (8.4 g, P = 0.80), S ADL (2.6 g; P = 0.88), C NDF (8.0 g; P = 0.23), C ADF (5.5 g; P = 0.26), or C ADL content (3.2 g; P = 0.33). S and C digesta data were calculated as a ratio (S:C) to evaluate fiber disappearance in GI tract. However, there was no effect of treatment on S:C NDF (1.6:1; P = 0.43), S:C ADF (1.6:1; P = 0.42), or S:C ADL (1.4:1; P = 0.34). Despite lack of differences, ADG was greatest (P < 0.05) from 25% HSM (35.1 g ± 1.16), least from 75% HSM (20.7 g ± 1.20), and intermediate from 0% (30.5 g ± 1.20) and 50% HSM (33.2 g ± 1.16). Data interpreted to mean that HSM may be a viable feedstuff in rabbit diets up to 50% without detrimental effects.